2018
DOI: 10.1016/j.jhsa.2017.08.031
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Radial Head Prosthesis Removal or Revision: A Systematic Review and Meta-Analysis

Abstract: Prognostic II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 40 publications
(37 reference statements)
3
32
0
Order By: Relevance
“…We were not able to assess the exact progression of radiological parameters, because plain radiographs were not carried out routinely between the postsurgical follow-up and our final follow-up. In conclusion, we believe that the use of bipolar implants in complex elbow injuries can be considered reliable if an accurate treatment of injured soft tissues is performed and if an optimal primary stability of the stem is reached, even with the use of cementation if needed; indeed, the role of soft tissues repair is strongly underscored in the most recent literature as instability represents one of the main causes of implant revision [24]. Most of the time, instability is related to LCL complex failure and lateral ligaments suture in addition to the radial head prosthesis can translate into much better outcomes (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We were not able to assess the exact progression of radiological parameters, because plain radiographs were not carried out routinely between the postsurgical follow-up and our final follow-up. In conclusion, we believe that the use of bipolar implants in complex elbow injuries can be considered reliable if an accurate treatment of injured soft tissues is performed and if an optimal primary stability of the stem is reached, even with the use of cementation if needed; indeed, the role of soft tissues repair is strongly underscored in the most recent literature as instability represents one of the main causes of implant revision [24]. Most of the time, instability is related to LCL complex failure and lateral ligaments suture in addition to the radial head prosthesis can translate into much better outcomes (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Despite we reported satisfactory clinical outcomes, the need of second surgery in 5 out of 17 patients is not neglectable, with an overall rate of 29.4% and a removal rate of 17.6%, higher than that reported in the current literature. Indeed, in a systematic review and metaanalysis, Kachooei et al [24] found a pooled rate of radial head prostheses removal or revision of 10%; more than half of the implants were revised for excision of heterotopic ossifications (47%) and for the treatment of elbow stiffness and limitation of the range of motion (42%); other relevant causes were pain (19%), aseptic loosening (16%), overstuffing (13%) and instability (12%). In our series, the primary indication for removal was an early aseptic symptomatic loosening of the prostheses; after two months both patients presented type IV radiolucencies surrounding uncemented stems (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This data would suggest that monopolar prostheses provide significantly greater radiocapitellar stability when used in the treatment of terrible triad injuries, than bipolar implants. These findings have been replicated in multiple clinical studies, though without statistically significant evidence, and the monopolar implant is currently the device of choice in cases of associated soft tissue injury [12,[58][59][60][61][62][63].…”
Section: Revolutionmentioning
confidence: 95%
“…Sahu et al [62] showed that anatomic RHP with articular surfaces that match the radius of curvature of the capitellum have increased radiocapitellar contact areas and lower peak pressures compared to mono-and bipolar implants. Although comparative clinical studies could not reproduce these results, the use of the anatomic RH is recommended to avoid long-term cartilage damage; the polarity of the design does not appear to affect this endpoint [12,51,[59][60][61][62][63].…”
Section: Revolutionmentioning
confidence: 99%
“…Despite a plethora of clinical outcome studies, no design has shown clinical superiority. 2,6,13 In general, short and mid-term clinical outcomes are mostly good but long-term results are still poorly documented. 3,8 Some biomechanical studies have suggested less joint stability after bipolar prostheses 5,18 with increased elbow valgus laxity.…”
Section: Introductionmentioning
confidence: 99%